E-commerce in Europe: Parcel delivery prices in a digital single market - J. Scott Marcus; Georgios Petropoulos (Bruegel, 2016)
In its Digital Single Market strategy, the European Commission has rightly noted the importance of reducing the price paid for basic cross-border parcel delivery by consumers and by small and medium size retail senders. The payment flows for cross-border parcel delivery are strikingly similar to those for telecommunications. Comparisons with roaming can be instructive. As with roaming, it is clear that the links between wholesale payments between the national postal operators and retail prices need to be properly understood in order to craft good policy. Another useful lesson is that national postal regulatory authorities are unlikely to address cross-border problems because of limitations in their respective mandates and because they have no incentive to take measures to benefit residents of other countries. There are also significant differences between roaming and parcel delivery. While high wholesale charges were a major driver of high retail prices for international mobile roaming, the wholesale payments for cross-border parcel delivery appear to be below cost. This implies that it is the 'spread' between retail price and the wholesale payment that is inflated, at least for small retail senders and for consumers. Comprehensive statistics gathering, coordinated at European level, is indispensable.
Keywords: 330